Effect of micronutrient on growth attributes, yield and economics of linseed under limited irrigation: Effect of micronutrient on growth attributes, yield and economics of linseed under limited irrigation - J R KATORE; BEENA NAIR; RUPALI DAMDAR; SHILPA RANANAWARE; S R KAMDI; G R KAVALKAR (Journal of Oilseeds Research, 2020)
Plant height, number of branches and number of capsules/plant were significantly greater with soil application of ZnSO4 (25 kg/ha) and borax (1.5 kg/ha) at the time of sowing. Seed yield, gross returns and net returns followed the similar trend. Seed yield was at par with foliar application of ZnSO4 and boron.